Genome mining as a biotechnological tool for the discovery of novel biosynthetic genes in lichens - Singh, Garima; Dal Grande, Francesco; Schmitt, Imke (Frontiers in Fungal Biology, 2022)
Natural products and their derivatives are a major contributor to modern medicine. Historically, microorganisms such as bacteria and fungi have been instrumental for generating drugs and lead compounds due to the ease of culturing and genetically manipulating them. However, the ever-increasing demand for novel drugs highlights the need for bioprospecting unexplored taxa for their biosynthetic potential. Advance in next-generation sequencing technologies has expanded the range of organisms that could be exploited for their biosynthetic potential as it is culture-independent and provides a glimpse of organisms’ entire biosynthetic potential. This could then be compared to the pre-characterized biosynthetic genes to identify the ones potentially coding for novel products. In this study, we mine the genomes of nine lichen-forming fungal species of the genus Umbilicaria for biosynthetic genes, and categorize the BGCs as “associated product structurally known”, and “associated product putatively novel”. Although lichen-forming fungi (LFF) have been suggested to be a rich source of natural products, it is not known how their biosynthetic diversity compares to bacteria and fungi. We found that about 25-30% of the biosynthetic genes are divergent when compared to the global database of BGCs comprising of 1,200,000 characterized biosynthetic genes from planta, bacteria and fungi. Out of 217 total BGCs, 43 were only distantly related to known BGCs, suggesting they encode structurally and functionally unknown natural products. Clusters encoding the putatively novel metabolic diversity comprise PKSs (30), NRPSs (12) and terpenes (1). Our study emphasizes the utility of genomic data in bioprospecting microorganisms for their biosynthetic potential and in advancing the industrial application of unexplored taxa. We highlight the untapped structural metabolic diversity encoded in the lichenized fungal genomes. To the best of our knowledge, this is the first investigation identifying genes coding for NPs with potentially novel therapeutic properties in LFF.